Effect of timolol maleate on pacing induced myocardial ischaemia. Issue 6 (December 1984) - Daly, K; Richardson, P J; Bergman, G; Atkinson, L; Kerkez, S; Jewitt, D E
Abstract : The effects of timolol maleate administered intravenously on coronary and systemic haemodynamics, myocardial metabolism, and plasma catecholamine concentrations were assessed in 10 patients with confirmed coronary artery disease. Rapid atrial pacing to the onset of angina was performed in all patients. Timolol reduced cardiac output at rest and during pacing and reduced resting heart rate but did not affect arterial blood pressure. Left ventricular stroke work index fell during pacing. Coronary sinus blood flow was unchanged, but pulmonary artery diastolic pressure rose after timolol. The drug produced clinical improvement in nine of the 10 patients with prolongation of the mean pacing time to angina. There was evidence of improved myocardial metabolism with a change from production to extraction of lactate: Arterial noradrenaline concentrations at rest rose after timolol. In these patients with coronary artery disease timolol produced an increased tolerance to atrial pacing stress, which appears to be due to a combination of effects including reduced myocardial contractility and decreased lipolysis.